Implementation of Early Mobilization to Reduce Pain Intensity Post-Cesarean Section at Labuang Baji Regional General Hospital - Kasim, Erna; Fitri, Fitri; Limbong, Magdalena; Ahmad, Ekayanti Hafidah; Kessi, Andi Tenriola Fitri (Genius Journal, 2024)
Introduction: Cesarean section (Sectio Caesarea) is a surgical procedure involving the removal of the fetus through an incision in the abdominal and uterine walls. Objective: To implement early mobilization as a strategy to reduce pain intensity following a cesarean section at Labuang Baji Regional General Hospital, Makassar. Method: A descriptive case study was conducted involving two respondents. Results: On the third day post-surgery, both respondents initially experienced moderate pain intensity. After the implementation of early mobilization, pain intensity decreased to mild levels. Conclusion: The case study concluded that early mobilization effectively reduces pain intensity in post-cesarean section patients.